(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
Biomorphological structure of coenofloras of pioneer vegetation of Ukraine was analysed in the system of K.Raunkiaer life forms organization. Classes Thero-Salicornietea, Crypsidetea aculeatae, Crithmo-Staticetea, Ammophiletea, Cakiletea maritimae, Isöeto- Nano-Juncetea, Bidentetea, Koelerio-Corynephoretea and Festucetea vaginatae were provided. It total 844 species belong to 79 families and 338 genera. It was established that 10 leading families, which constitute 72,8 % of the total number of species represented by hemicryptophytes – 285 species, or 71,7 % of the total amount; terophytes – 202 (77,1 %), geophytes – 56 (57,6 %) heliophyte – 22 (48,9 %), hamephytes – 16 (69,6 %) and fanerophytes – 3 (15 %) species. The occurrence of species of life forms on the leading families of synanthropic and native factions in these classes was compared. It was revealed that the ratio between species is: fanerophytes – 1:0,5, hemicryptophytes – 1:0,41, geophytes – 1:0,13, helophytes – 1:0,16 and terophytes – 1:1,15. In the group of hamephytes only native species are presented. Comparison of the distribution of species with a single life forms, in general, showed similarities in coenofloras of pioneer vegetation to arid zone flora, within native faction – with humid. Groups of coenofloras clusters grouped according biomorfologichnmy featured species. It is shown that biomorphs of the Festucetea vaginatae differ significantly from such of the Koelerio-Corynephoretea. So, there is no reason to combine these groups into a single class. Biomorphological structure of coenofloras of pioneer vegetation of Ukraine reflects the current state of their ecological and historical stage of development and can be taken to compare and determine the extent of further transformation of communities under the influence of natural and anthropogenic factors and, in particular, of global warming.